AN ANALYSIS OF MOOD SELECTION IN STUDENTS' EXPOSITION - Wiwoho, Gurendi (LINGUAMEDIA Journal, 2024)
This study purposes to analyze student expository writing. The focus of the analysis is on the realization of interpersonal meanings in their texts. The data collected were five student expository texts that they composed based on classroom assignment. By applying functional approach, the data analysis used tabkes and lexico-grammar to describe elements of Mood selections within the clauses in the texts.  The results show that all mood elements such as MOOD TYPE, MOOD PERSON, DEICTICITY, POLARITY and MODALITY altogether indicates how the students  realize interpersonal meanings in their texts with various degrees of finiteness and problems in each element. The results also indicate that at least 41.44 per cent of the cases identified are concerned with the finiteness of the propositions. It means they still made mistakes in the mood structure, such as missing finite, missing or unclear subject,  and mis-ordering of subject and finite  There are actually other problems with the texts, such as punctuation, capitalization and spelling but not discussed in this study. Keywords: Mood selection, functional,  expository text,.